Pentagon theory dan model beneish M-score - Zahra Anggreini, Syavinda; Himmawan D. N, Arief (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Fraudulent financial reporting is defined as fraud committed by the management of a company by providing a false picture of the financial statements, which, of course, harms investors and other related parties. This research aims to analyze the effect of fraud using the pentagon theory. The Pentagon fraud theory is measured by financial targets, financial stability, external pressure, institutional ownership, ineffective monitoring, changes in KAP, changes in directors, and the number of photos of members. President, Director The sampling method used is purposive sampling. The sample consists of 41 companies from 168 manufacturing companies that are the research population for 2018–2020. This study shows that the financial target variable has an effect on financial reporting fraud, while financial stability, external pressure, institutional ownership, ineffective supervision, KAP changes, director changes, and the number of photos of the main director have no effect on fraudulent financial reporting.